A comprehensive, bed-side scoring system to predict difficult lumbar puncture - Shobha Subramanian; B M Reshma; M Salim Iqbal; S S Harsoor (Wolters Kluwer Medknow Publications, 2023)
Background and Aims: Spinal anesthesia (SA) is the most widely practiced neuraxial anesthesia. Lumbar puncture (LP) at multiple levels and multiple attempts due to any reason may cause discomfort and even serious complications. Hence the study was conducted to evaluate the patient variables that can predict difficult LP thus allowing for the use of alternate techniques. Material and Methods: We included 200 patients of ASA physical status I-II, scheduled to undergo elective infra-umbilical surgical procedures under spinal anesthesia. During preanesthetic evaluation, difficulty score was assessed using the 5 variables: Age, abdominal circumference, spinal deformity - assessed as axial trunk rotation (ATR) value, anatomical spine assessed by spinous process landmark grading system (SLGS) and patient position, by assigning a score of 0- 3 for each variable, with a total score of 0 - 15. The difficulty of LP was graded as easy, moderate or difficult based on total number of attempts and spinal levels by independent experienced investigator. The scores obtained during preanesthetic evaluation and the data collected after performing LP were analyzed using multivariate analysis and P value noted. Results: Our study showed that above patient variables correlated well with difficult LP scoring (P < 0.001). SLGS was noted to be a strong predictor, while ATR value a weak predictor. The correlation between the total score and grades of SA had a positive association (R = 0.6832, P < 0.00001) and was statistically significant. A median difficulty score of 2, 5 and 8 predicted easy, moderate and difficult LP respectively. Conclusion: The scoring system provides for a useful tool to predict difficult LP and helps both patient and anesthesiologist to choose an alternative technique.